Influence of micro and macroroughness of geomembrane surfaces on soil-geomembrane and geotextile-geomembrane interface strength - Araújo, Gregório Luís Silva; Sánchez, Nelson Padron; Palmeira, Ennio Marques; Almeida, Maria das Graças Gardoni de (Geotextiles and geomembranes, 2022)
The interface shear strength involving geosynthetics and other materials can be influenced by various parameters, such as the material type and the normal stress on the interface. Although several investigations have been conducted over the years on this topic, the large variation of interfaces that can be used has led researchers to develop other sources of information to improve design methods. This paper investigates how roughness parameters can influence the shear strength developed between different interfaces based on many inclined plane tests and microscopic analyses of the surface roughness. One smooth and three textured geomembranes were used to simulate a barrier layer and sand, and two nonwoven geotextiles were installed on them to simulate drainage or protective layers. A powerful optical apparatus provided fifteen bidimensional and tridimensional surface parameters for the two faces of the analyzed geomembranes. The results showed that the mean height of profile elements (Rc) and the core material volume (Vmc) parameters presented stronger correlations with the interface shear strength. The concept of interface roughness factor was introduced to estimate the interface friction between different materials based on the materials properties for interfaces with geotextiles. •Inclined plane tests were performed with different types of geomembranes covered by sand and geotextiles.•Geomembranes roughness parameters were measured by means of a powerful 3D optical microscope.•Several parameters can be applied to improve the geomembranes characterization.•Interface Roughness Index is proposed in order to predict the interface shear strength behavior.